2011
DOI: 10.1007/s13313-011-0107-1
|View full text |Cite
|
Sign up to set email alerts
|

Combination of endophytic bacteria and resistant cultivars improves control of Ralstonia wilt of tomato

Abstract: The aim of this study was to evaluate the combined effect of endophytic bacteria and tomato cultivars with different resistance levels to Ralstonia solanacearum in the control of tomato bacterial wilt. Endophytic bacteria were successfully introduced into tomato seedlings by three methods: cutting of the hypocotyl, substrate drenching and seed microbiolization. One hundred and fifty endophytic bacterial isolates were screened in greenhouse assays. Two isolates, identified as Bacillus sp. and Serratia marcescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…A previous study reported that the combination of endophytic bacteria ( Bacillus sp. and Serratia marcescens , both of which had no antibiosis) with resistant cultivars of the tomato reduced the incidence of bacterial wilt ( 18 ).…”
Section: Methods Used For Crop Protectionmentioning
confidence: 99%
“…A previous study reported that the combination of endophytic bacteria ( Bacillus sp. and Serratia marcescens , both of which had no antibiosis) with resistant cultivars of the tomato reduced the incidence of bacterial wilt ( 18 ).…”
Section: Methods Used For Crop Protectionmentioning
confidence: 99%
“…A prior study found that the prevalence of bacterial wilt was decreased when resistant cultivars of the tomato were combined with endophytic bacteria (Bacillus sp. and Serratia marcescens, both of which displayed no antibiosis) (Barretti et al, 2012). In IPM for soil-borne diseases, grafting is a key tactic.…”
Section: Integrated Pest Management (Ipm)mentioning
confidence: 99%
“…Since organic farming is gaining momentum, ecofriendly biological control measures are highly preferable to chemical control which poses serious environmental threats. Several rhizobacteria, endophytic bacteria, actinomycetes, phages etc were evaluated for bacterial wilt management in many economically important crops ((Lemessa and Zeller, 2007;Yamada et al, 2007;Ramesh et al, 2009;Barretti et al, 2012;Achari and Ramesh, 2014;Yuan et al, 2014)). In ginger, the common strategies adopted for bacterial wilt management include selection of disease free rhizomes, selection of fields with no history of bacterial wilt, seed treatment using chemicals, strict phytosanitory measures to avoid the carryover of pathogen inoculum through field workers or irrigation water and crop rotation with non-host plants (Kumar and Hayward , 2005).…”
Section: Introductionmentioning
confidence: 99%